(untitled) (Experimental biology, 2021)
Currently, cryopreservation of fish reproductive cells is an urgent direction in the strategy of preserving genetic biodiversity, as well as the development of fisheries and aquaculture, scientific research was carried out in the research center "Fisheries" of the «S.Seifullin Kazakh Agro Technical University» and in the JSC "Republican Center for Breeding in Animal Husbandry "Assyl Tulik" in 2021. During the research, the method of cryopreservation of male carp reproductive cells using two types of cryoprotector based on 10% ethylene glycol and 10% dimethyl sulfide oxide was studied. During the experimental work, the generally accepted methods for conducting fish bonitization and freezing carp sperm were used. The assessment of the quality of carp sperm was carried out on a 5-point Persov scale. Also, when assessing the quality, the volume, concentration of sperm, the time of activity and mobility of carp sperm were taken into account. As a result of scientific research, it was found that the use of a cryoprotective medium consisting of 10% ethylene glycol has a positive effect in comparison with DMSO, since it reduces the osmotic and oxidative stress experienced by cells during freezing. The obtained results allow us to recommend adjusting the concentration of penetrating protectors in the cryoprotective solution depending on the amount of intracellular water to increase the survival rate of male fish reproductive cells after a double temperature shock. The results of the research make it possible to create a cryobank of the gene pool of carp breeding material at fish hatcheries to preserve the genetic diversity of these commercial objects.